Migrations of the sublime: from the labyrinthine space to the time of disaster (Palíndromo, 2026)
This article explores the sublime as an iconological category, tracing the migrations of its visual and narrative formulas from Piranesi's anguish to the sublime of contemporary disaster. From Piranesi's Carceri — a paradigm of vertigo and disorientation — to the montages of temporal fractures in Hanne Darboven's work (Kulturgeschichte) and to the catastrophic images reworked by Tacita Dean (The Russian Ending), the sublime is reconfigured as an aesthetic and critical experience of the historical immeasurable. In dialogue with the reflections of Warburg and Didi-Huberman, this article seeks to show how images of the sublime, between past and present, still offer decisive interpretative keys today. From this perspective, the survival of images cannot be explained by formal or symbolic continuity, but rather by the persistence of an energetic charge — a true Lebensenergie — that traverses time and reappears in displaced and fragmented forms.
Keywords: Sublime; Labyrinth; Catastrophe; Survival; Lebensenergie